Mediator release after nasal aspirin provocation supports different phenotypes in subjects with hypersensitivity reactions to NSAIDs - Campo, P.; Ayuso, P.; Salas, M.; Plaza, M. C.; Cornejo‐García, J. A.; Doña, I.; Torres, M. J.; Blanca‐López, N.; Canto, G.; Guéant, J.‐L.; Sanak, M.; Blanca, M. (Allergy (Copenhagen), 2013)
Background Multiple NSAID‐induced urticaria/angioedema (MNSAID‐UA) is an entity well differentiated from aspirin‐exacerbated respiratory disease (AERD), although no detailed phenotype analysis has yet been performed. The objective was to evaluate the functional characteristics of MNSAID‐UA subjects by analyzing the response to nasal lysine–aspirin challenge and measurement of nasal inflammatory mediator release compared with AERD subjects and controls. Methods The study included 85 subjects with confirmed hypersensitivity to NSAIDs (≥3 episodes with >2 different NSAIDs or positive drug provocation) with either cutaneous (MNSAID‐UA, n = 25) or respiratory manifestations (AERD, n = 60) and 30 tolerant controls (15 aspirin‐tolerant asthmatic patients and 15 healthy controls). Nasal lavages at 0, 15, 60, and 120 min after lysine–aspirin challenge were analyzed for ECP, tryptase, PGE2, PGD2, LTD4, and LTE4. Results Lysine nasal challenge was positive in 80% of the AERD cases but positive only in 12% of the MNSAID‐UA group. MNSAID‐UA subjects showed no changes in nasal ECP, whereas subjects with AERD had increased levels of ECP, with the highest peak at 15 min after challenge (P < 0.05). Tryptase levels were higher in AERD compared with MNSAID‐UA and controls with the highest release of tryptase at 60 min (P < 0.05). Significant increases in PGD2, LTD4, and LTE4 were observed in AERD (at 60 min for PGD2, LTD4, and LTE4) but not in MNSAID‐UA or control subjects (P < 0.05). Conclusions Data support the observation that MNSAID‐UA, although sharing a common response with AERD to COX inhibitors, seems to have a distinctive phenotype, based on the response to nasal challenge and the release of inflammatory mediators.